DESENVOLVIMENTO DE PRODUTOS BIOTECNOLÓGICOS PARA O CONTROLE DO CARRAPATO BOVINO Rhipicephalus (Boophilus) microplus - SOUSA, Isabella Chaves (2022)
Rhipicephalus (Boophilus) microplus (Acari: Ixodidae), popularly known as cattle tick, is considered the main ectoparasite in tropical and subtropical countries. The control of this tick is carried out mainly by the use of synthetic acaricides, and numerous reports of resistant populations are described worldwide. Given this scenario, it is essential to develop new products for the control of this parasite, as well as new methods that assess with greater precision and less subjectivity the tick resistance and the selection of potential drugs for the control of R. (B.) microplus. The present study was divided into two chapters. Chapter I aimed to develop and validate a new automatic counting method to assess tick larval mortality. A software for differentiating live and dead larvae was developed in different stages: obtaining videos; image segmentation using the firefly algorithm; larvae detection with the fast radial symmetry transformation (FRST) technique; and tracking of larvae based on particle displacement over time. To validate the developed software, larval immersion tests of R. (B.) microplus with ivermectin, cypermethrin and fipronil were performed in triplicate. The assessment of larval mortality was performed by recording videos at 60, 40 and 20s for further analysis in the counting software. In addition, manual counts of the same samples were performed by three different analysts, each responsible for counting a replica of each test. There was no statistical difference in LCs50 determined in manual and automatic assessments for ivermectin and fipronil. For cypermethrin, the LC50 calculated after manual assessment was 2.2 times lower than that of automatic assessment. Video acquisition time was 2.9 to 4.4 times faster than manual evaluation. The average processing time for each video was 5.73 min, regardless of their duration. Chapter II aimed to evaluate the in vivo and in vitro acaricide activity of a formulation containing synthetic pyrethroid associated with a monoterpene. From the associations between the monoterpene and the pyrethroid, in vitro tests were carried out on R. (B.) microplus larvae, verifying a possible synergism. In the in vitro test of engorged females, the formulation with the association of pyrethroid + monoterpene (0.4 mg/mL) presented a percent control of 57.50%, a value higher than that obtained with the formulations with pyrethroid alone. In the in vivo tests, the association of pyrethroid + monoterpene (0.4 mg/mL) presented an average percent control (67.3%) higher than the formulation with only pyrethroid (57.7%), with the best results. visualized between days +1 and +7, when the percentage of control presented values of 93.75% and 71.84%, compared to 50.20% and 40.05% of the pyrethroid formulation alone. According to the results obtained in this study, we demonstrate that the method developed for automatic counting of tick larvae was validated and can be considered a viable alternative for determining the percentage of tick larvae mortality. Furthermore, the formulation developed in this work (synthetic pyrethroid + monoterpene) has the potential to be used in the control of R. (B.) microplus and should be considered as a basis for further studies.